Diploidization of cucumber (Cucumis sativus L.) haploids by colchicine treatment - Vesselina Nikolova; Katarzyna Niemirowicz-Szczytt (Acta Societatis Botanicorum Poloniae, 2014)
Haploid cucumber plants are totally infertile and do not undergo spontaneous diploidization. The use of haploids depends on the possibility of doubling the chromosome number and the obtaining of stable doubled haploids (DH). Four haploids of different genotypes propagated vegetatively were treated with colchicine in order to obtain DH. The following procedures were used: 1) apical shoot meristem treatment, 2) soaking of shoot explants, 3) placing of shoot explants on medium with colchicine. Plants of the C1 generation were evaluated in respect to morphological and cytological characters and fertility. The best result of 20.9% DH was obtained after repeated treatment of the meristem with colchicine. A large group of chimeras (28.5%) was also distinguished as were haploids and tetraploids. DH plants were fertile and gave uniform progeny. Chimeras had a decreased fertility and showed disturbances in meiotic divisions.